PENGARUH SIKAP DAN NORMA SUBYEKTIF MASYARAKAT KOTA DENPASAR TERHADAP NIAT BELANJA PADA PASAR TRADISIONAL - Ni Made Rastini (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2013)
This research was conducted by taking 100 respondents in the traditional markets of Denpasar traditional market. Data was collected using questionnaires. The variables measured from the sample consist of  evaluation of the beliefs, subjective norm and the influence on the intend to shop in traditional markets in Denpasar regency.  The results of regression analysis found that the evaluation of beliefs and subjective norms  affect consumers’ shopping intentions in a traditional market, in which subjective norms variable are more dominant affecting the spending intentions